Study of the Effect of Groove Shape to Improve Bogie Bushing Performance Using CFD Simulation Approach - Umar, Siproni; Sutanto, Hadi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The simulation analysis approach aims to conduct CFD (Computational Fluid Dynamics) simulation analysis on bushings with different groove shapes in an effort to improve lubrication efficiency. This study is basically a 3D modeling approach and then uses Computational Fluid Dynamics simulation which is a method used to model, analyze, and related phenomena in a system with a numerical approach. The addition of grooves to the bushing surface can affect the flow of lubricant around it. Through CFD simulation, the author will compare the performance of various groove designs to identify models that provide better lubrication. The results of this study are expected to provide valuable insights into the development of more lubricating efficient bushings.